DIFFERENT TESTING OF THE PREDICTION OF BANKRUPTCY OF HEALTH SECTOR SERVICES (HOSPITALS) LISTING ON BEI BEFORE COVID-19 PANDEMIC AND COVID-19 PANDEMIC WITH SPRINGATE METHOD - Lardin Korawijayanti; Rudi Handoyono; Fatchur Ridho (Politeknik Negeri Semarang, 2022)
The pandemic Covid-19 has the impact of changing financial conditions that can result in bankruptcy. Bangkruptcy is the failure of company in carriying out its operational activities to generate profits and failure to pay obligations. One of the signs before the occurrence of bankruptcy in a company is financial distress. Financial distress can be seen from thefinancial statements which are a reflection of the financial condition and results of company, financial statements that can be compared in the data regarding changes that occur in the form of percentages trends and rupiah. The study aims to determine the differences in prediction of healthcare service companies (hospitals) before the pandemic Covid-19 and during the pandemic Covid-19. The population in this study are healthcare service companies (hospital) listed on the IDX for the 2019-2020 period. Samples were selected using purposive sampling method. Hypotesis testing using a different paired 2 test. The results of this study indicate that before the pandemic Covid-19 there were 2 healtcare service companies (hospitals) in the non-bankruptcy category and 5 other companies in the bangkrupt category. Meanwhile, during the pandemic Covid-19, 3 healthcare service companies (hospitals) were not bankrupt category and 4 other companies in the bangkrupt category. This study also shows that there is a significant difference between the value of the bankruptcy ratio of healthcare service companies before the pandemic Covid-19 and during the pandemic Covid-19.